2018
DOI: 10.1186/s40748-018-0092-2
|View full text |Cite|
|
Sign up to set email alerts
|

Association between furosemide in premature infants and sensorineural hearing loss and nephrocalcinosis: a systematic review

Abstract: Furosemide is a potent loop diuretic commonly and variably used by neonatologists to improve oxygenation and lung compliance in premature infants. There are several safety concerns with use of furosemide in premature infants, specifically the risk of sensorineural hearing loss (SNHL), and nephrocalcinosis/nephrolithiasis (NC/NL). We conducted a systematic review of all trials and observational studies examining the association between these outcomes with exposure to furosemide in premature infants.We searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 71 publications
(155 reference statements)
2
11
1
Order By: Relevance
“…Regardless, no relationship between the administration of high doses or prolonged treatment and the need to discontinue the therapy was evident. The low rate of adverse event is in line with a recent review that found low evidence for the risk of SNHL and NC/NL in premature infants [37].…”
Section: Discussionsupporting
confidence: 84%
“…Regardless, no relationship between the administration of high doses or prolonged treatment and the need to discontinue the therapy was evident. The low rate of adverse event is in line with a recent review that found low evidence for the risk of SNHL and NC/NL in premature infants [37].…”
Section: Discussionsupporting
confidence: 84%
“…Sensorineuronal hearing loss is more frequent in infants born preterm vs. term, and the earlier the gestational age at birth, the greater the risk. The proposed mechanisms for the increased risk of hearing loss have largely focused on postnatal factors, such as immaturity, administration of ototoxic medications (e.g., aminoglycosides, diuretics), environmental noise, hyperbilirubinemia, and hypoxia [295][296][297][298]. However, the role of congenital factors has been known since 1897 when Aschoff described the concept of otitis media neonatorium, which was thought to be a sterile middle ear inflammation related to aspiration of amniotic fluid cellular content based on microscopic study of the temporal bone in fetuses and neonates [299].…”
Section: Earsmentioning
confidence: 99%
“…In pediatric patients, recommended dosing of furosemide is 1 mg/kg/dose up to a maximum of 6 mg/kg/dose [4]. In premature infants, the maximum US Food and Drug Administration label suggested dose is 1 mg/kg/day [4, 13]. Despite these recommendations, current dose and frequency practice varies widely [11].…”
Section: Introductionmentioning
confidence: 99%